The english language learning in russian and japanese classrooms; 3rd International Multidisciplinary Scientific Conference Social Sciences and Arts (SGEM2016); Bk. 1 : Psychology and Psychiatry, Sociology and Healthcare, Education Conference Proceedings, vol. 3 - Kazantseva G. S. Galina Semenovna; Kazantsev A. Yu. Andrey Yurievich; Kruglikova M. E. Margarita Evgenjevna; Solodovnikova O. V. Olga Vladimirovna (2016, 2016)
With global interdependencies that require multilateral cooperation among countries, the importance of teaching and learning English is invaluable. However, the general level of English of school leavers and university students is low both in Russia and Japan. This study investigates the situation regarding the English language learning in Japanese and Russian classrooms. The observations suggest that there is a certain drawback in English education in both countries. The materials analyzed testify to the fact that students learning English for a long period of time at school then at university make little progress especially in oral communication. There was therefore a compelling need for us to undertake this research concerning this problem. Through drawing the analogy in learning and teaching a second language between these neighboring countries, we conducted the survey among students of one of the leading universities in Russia in search of the reasons which would account for the current situation. The empirical data have been drawn from a survey of over 70 Russian university students. The results indicate that students in this study share some ideas about English, including their perceptions of their English learning experience, to which they responded negatively. The findings of the survey carried out open up some serious pedagogical questions. We have made some recommendations on the second language teaching improvement.